Resin Duct Anatomical Structure of High Resin Yielder Pinus merkusii - Arida Susilowati; Imam Wahyudi; Supriyanto Supriyanto; Iskandar Z Siregar; Corryanti Corryanti; Apri H Iswanto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The objective of this research was to characterize resin duct anatomical structure of high resin yielder pine (Pinus merkusii) that influences resin production. Samples were collected from high resin yielder pine with different resin production class from seedling seed orchard Cijambu, Sumedang and normal trees from Bogor. Samples than evaluated through microscopic and macroscopic observation to get information about some parameter related to resin duct. The result on anatomical structure characterization showed that high resin yielder trees compared to that of normal one are as followed: darker in wood colour (reddish brown compared to creamy white), higher in number of axial resin duct (9.401.68 mm-2 to 101.30 mm-2 compared to 40.96 mm-2), wider in resin duct diameter (468.8998.72 μm to 562.11181.62 μm compared to 109.4211.26 μm), thicker in epithelium cell (50.81 12.20 μm to 58.599.55 μm compared to 23.1787 μm). These differences may affect to quantity of resin yielder compared to normal producer.Key words: anatomical structure, epithelium, high resin yielder, Pinus merkusii, resin duct